Management of powdery mildew of mustard - R.N. SINGH, R.B. SINGH and (Indian Phytopathology, 2003)
Erysiphe cruciferarum incited powdery mildew of mustard (Brassica juncea) has aggravated during recent years in late sown crop in Uttar Pradesh. Disease occurs between second week of February to first week of March. Eight resistant donors, namely, DIR 621, IJWHJ 001, PCR 10, PCR 9201, RK 8602, RK 8615,RAUD 101 and YSPB 24 alongwith 20 moderately resistant sources, CSTR 610-10-15, DIR 513, DLM 50, NRJ 14, PBR 106, RE 5, RK 9402, RJ 16, RL 91-24, RH 9301, RSK 74, SKM 9328, TM 26, TM 18-8, VMR 1-2, YSBW 871, YSBW 881, NDYS 17, YST 151 and SSK 92-3, have been identified. Three sprays of aquous suspensions of Triadimefon 25 WP (0.1%), Tridemorph 80 EC (0.1%), Dinocap 48 EC (0.075%) and Wettable Sulphur 80 WP (0.3%), at 15 day intervals, after disease appearance, controlled the disease effectively and increased seed yields. Triadimefon proved most effective and Wettable Sulphur most economical.